How Does Financial Literacy Mediate the Relationship Between Tax Knowledge, Ethnicity Issue, and Trust in Government on Tax Compliance? - Berlina Hidayati (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2026)
This study investigates the determinants of tax compliance by integrating cognitive, socio-cultural, and institutional factors within a unified analytical framework. Specifically, it examines the direct effects of tax knowledge, ethnicity issue, and trust in government on tax compliance, as well as the mediating role of financial literacy. Using a quantitative research design, primary data were collected through online questionnaire administered to 359 respondents. The data were analyzed by Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings indicate that tax knowledge and ethnicity issue significantly and positively influence tax compliance, whereas trust in government does not show a significant effect. Moreover, financial literacy significantly mediates the relationship between tax knowledge and tax compliance but fails to mediate the effects of ethnicity issue and trust in government. These findings suggest that financial literacy operates as a selective mediator, primarily translating knowledge into compliant behavior through cognitive pathways, while socio-cultural and institutional factors influence compliance through alternative normative mechanisms. This study contributes by proposing a nuanced behavioral model that differentiates competence-based and perception-based drivers of tax compliance, offering important implications for multidimensional tax policy design in developing and multicultural contexts.